The ubiquitous camera: An in-depth study of camera phone use - Kindberg, Tim; Spasojevic, Mirjana; Fleck, Rowanne; Sellen, Abigail (IEEE Pervasive Computing, 2005)
An in-depth study produced a six-part taxonomy that describes how people use camera phone images for social and personal purposes and affective and functional purposes. Reviewing the taxonomy reveals implications for future products and services.